การเตรียมและการศึกษาลักษณะเฉพาะทางไฟฟ้าของฟิล์มบางคอปเปอร์อินเดียมไดซีลีไนด์ - ชาญวิทย์ จิตยุทธการ (จุฬาลงกรณ์มหาวิทยาลัย, 1995)
CuInSe2 thin films on glass substrates were prepared by two similar methods. The first method involved evaporation of CuInSe2 under high vacuum without substrate heating, followed by annealing under Se vapor in an evacuated or argon-filled stain less chamber at different temperatures. The second method involved co-evaporation of CuInSe2 and Se under high vacuum with substrate heating at different temperatures. The crystal structure of the films was found to be chalcopyrite structure by the results of the X-ray diffraction method. The thin films from the first method peeled off of the glass substrate, but the films from the other method were smooth and have an absorption coefficient of more than 105cm-1 with an energy gap of about 1.01 eV. CuInSe2 Thin films of n-type or p-type can be prepared by the second method with different substrate temperatures and deposition rates of selenium.